Risk-constrained offering strategy for a hybrid power plant consisting of wind power producer and electric vehicle aggregator - Gao, Xiang; Chan, Ka Wing; Xia, Shiwei; Zhou, Bin; Lu, Xi; Xu, Da (Energy (Oxford), 2019)
Renewable energy producers such as wind power producers (WPP) and electric vehicle (EV) aggregators are playing an increasingly important role in the electricity market as their large capacity could strategically influence the electricity price. This paper proposes a bi-level stochastic optimization model of offering strategy for an aggregated WPP-EV hybrid power plant (HPP) as a price maker in the day-ahead (DA) market while considering the uncertainties of the energy production and spot price in the real-time (RT) market. While the HPP's profits is maximized in the upper level of the proposed model with the use of conditional-value-at-risk (CVaR) to manage the risk of expected revenues, the social welfare from the perspective of the grid is maximized in the lower level. The formulated bi-level model is first transformed into a single-level mathematical program with equilibrium constraints (MPEC) and then further transformed into a mixed integer linear programming (MILP) problem for solution. Simulation results have demonstrated the effectiveness of the proposed HPP model with strategically bidding price to increase profits and reduce volatility of profits by considering the risk-metric. •EV aggregators with both V2G and G2V services and WPPs are integrated as a HPP.•A bi-level model of offering strategy for a HPP in the DA market is proposed.•Renewable energy production and real market prices are considered as uncertainties.•EVs and elastic loads as DR sources are price makers and price takers respectively.